Ewing Sarcoma Presenting as a Congenital Scalp Mass. (April 2019) - Haas, Jacqueline A.; Rice, Dahlia; Morrison, Clinton S.
Ewing sarcoma is a locally aggressive, highly malignant tumor most commonly seen in the skeletal system. The "Ewing family of tumors" also includes other tissue types that are not common, such as soft tissue origin classified as extraosseous Ewing sarcoma (EES) or primitive neuroendocrine origin. Age of onset most often occurs within the first 2 decades of life. Congenital presentation of EES is exceedingly rare. We report the first described case to our knowledge of congenital EES originating from the scalp.